A Comprehensive Literature Review of Mycobacterium tuberculosis Drug Resistance - Kharisma Bimo Cahya Nugroho; Ratri Ridha Sasanti (International Medical Journal Corp. Ltd, 2025)
Introduction: This review examines the global challenge of antimicrobial resistance (AMR), focusing on drug-resistant tuberculosis (DR-TB) as a major contributor to the global AMR burden. It provides an overview of the increasing threat posed by DR-TB and the need for advanced detection and management strategies. Methods: The review synthesizes current literature on DR-TB, particularly on resistance mechanisms, diagnostic advancements, and treatment strategies. It analyzes data from recent studies on gene mutations in Mycobacterium tuberculosis (M.tb) and the role of the bacterial cell envelope in resistance. Results: Key findings include the identification of genetic mutations linked to resistance to first- and second-line anti-TB drugs. The role of M.tb's cell envelope in drug resistance and host-pathogen interactions is also highlighted. Additionally, the review presents recent advancements in diagnostic tools, emphasizing the need for universal drug susceptibility testing and shorter, all-oral treatment regimens. Conclusion: The review underscores the challenges in diagnosing and treating DR-TB, including the need for improved diagnostic accuracy, accessibility, and treatment adherence. It emphasizes the importance of a multi-pronged approach, incorporating healthcare system strengthening, investment in new drug research, and global collaboration to achieve TB elimination by 2030.